Literature Review: Skin Aging in the Ederly Population - Salsabila, Baiq Ghefira Rojwani Putri; Hardiant, Excell Defry; Suryani, Elsa Indah; Salsabila, Tsania Zulfa; Savitri, Puti Amelia; Untari, Lania Pradiva; Paradiesta, Andi Frieskha Naurah; Angelita, Puja Rizkina; Adidaifa, Muhammad Fikri; Musyarof, Disa Fadil; Hidayatullah, Audi (Jurnal Biologi Tropis, 2025)
Skin aging is a progressive degenerative process characterized by a decline in the structural and functional capacity of the skin to maintain its protective, regenerative, and homeostatic roles. It is influenced by both intrinsic factors, such as genetics, telomere shortening, mitochondrial dysfunction, hormonal changes, microbiota alterations, and decreased vitamin D production, and extrinsic factors, including ultraviolet radiation, pollution, smoking, oxidative stress, and lifestyle. Clinically, skin aging presents with thinning, dryness, loss of elasticity, fine to deep wrinkles, pigmentary changes, and benign skin lesions. The increasing elderly population, particularly in Indonesia, highlights the growing importance of addressing skin aging due to its impact not only on physical health but also on psychosocial well-being and quality of life. Management strategies include pharmacological approaches such as sunscreens, moisturizers, vitamin D and collagen supplementation, retinoids, and hormone replacement therapy, as well as non-pharmacological interventions including antioxidant-rich nutrition, hydration, allergen avoidance, wound care, dietary restriction, facial massage, and aesthetic procedures like stem cell therapy. Early prevention, timely recognition, and comprehensive management of skin aging are essential to support healthy aging and maintain the quality of life among the elderly.